HUBUNGAN ANTARA KEBIASAAN MEMBACA PEMAHAMAN DAN BERPIKIR KRITIS PESERTA DIDIK KELAS III SD N SONOSEWU - Susi suryandari; Muhardila Fauziah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the relationship between reading comprehension habits and critical thinking skills of third-grade students at SD Negeri Sonosewu. This research employed a descriptive qualitative approach involving third-grade students, classroom teachers, and the school principal. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model with source triangulation. The findings indicate that students’ reading comprehension habits are in a good category, as reflected in their ability to identify main ideas, understand word meanings, draw simple conclusions, and relate texts to daily experiences. Students’ critical thinking skills also show positive development, including analyzing information, explaining cause-and-effect relationships, making simple judgments, and predicting outcomes. A supportive school environment, adequate literacy facilities, interactive learning strategies, and collaboration between teachers and parents play an important role in fostering these abilities. In conclusion, reading comprehension habits are closely related to the development of critical thinking skills in elementary school students. Keywords: Reading Comprehension Habits, Critical Thinking, Elementary School